Petroleum Fiscal Issues and Policies for Fluctuating Oil Prices in Vietnam - World Bank (Washington, DC, 2014)
The 1998 lowest level of international oil prices, triggered Viet Nam's request for technical assistance, to not only evaluate the petroleum fiscal system in comparison to other countries' competitiveness in international oil contracts' best practice, but also to evaluate options for flexible gas production contracts, including fiscal incentives for oil, and gas development of economically marginal fields. Since this report was prepared, in early 1999, oil prices have risen, and, the Petroleum Law was amended by mid 2000, hence, a later report will discuss revisions, and evaluate the total fiscal package. Nonetheless, the analyses reveal Viet Nam's contractual terms, concluding the country deals effectively with variations in economic conditions resulting from water depths; but ineffectively in dealing with field sizes, essentially creating the situation for small fields to remain uneconomic; moreover, it does not deal specifically with variations in economic conditions: actually it strongly discourages the development of fields with low-well productivity, deep wells, or high facility costs; and, although the country adequately deals with high oil prices, it does not deal effectively with low oil prices, instead, this instantly creates prevailing, uneconomic oil fields. Enhancements for flexible oil, and gas contracts, suggest rate of return sliding scales, and formulas based on cumulative production.